Is There a Role for the Therapeutic Drug Monitoring of Colistin? An Overview - Maria-Paula Avila; Tatiana Pacheco; Sara Arias; Rosa-Helena Bustos; Julio-Cesar Garcia; Diego Jaimes (Pharmaceuticals, 2020)
Colistin is used as a last-line antibiotic for the treatment of Gram-negative multiresistant bacteria. Due to its high nephrotoxicity, Therapeutic Drug Monitoring (TDM) is recommended for dose adjustment. We aimed to evaluate the available evidence of TDM in patients given colistin to treat Gram-negative infections. In this paper, we offer an overview, using an electronic search of the literature (published up to June 2019, without language restrictions) that compares the clinical outcomes and measurements of colistin TDM. Ultimately, the Therapeutic Drug Monitoring (TDM) of colistin in Plasma could prevent nephrotoxicity risk.